Accuracy of fine needle aspiration cytology in diagnosis of thyroid swelling - Hirachand, S; Maharjan, M; Lakhey, M; Thapa, R; Kafle, S (Journal of Pathology of Nepal, 2013)
Background: Fine needle aspiration cytology has been shown to be simple, safe, cost effective and quick to perform procedure with excellent patient compliance. It is a well established technique for preoperative investigation of thyroid gland swellings with high sensitivity, specificity and accuracy. The aim of this study was to determine the accuracy of fine needle aspiration cytology of thyroid swellings performed at our institution. Materials and Methods: This study was carried out at Kathmandu Medical College and Teaching hospital, department of Pathology over a period of 3 years (January 2010 to December 2012). Two hundred and seventy three patients of all age groups and both sexes who underwent fine needle aspiration cytology for thyroid swelling were evaluated. Out of 273 patients, histopathological diagnosis was available in 45 patients. Results: Fine needle aspiration cytology result revealed 245 cases (89.7%) as non-neoplastic, 21 cases (7.7%) as neoplastic and 7 cases (2.6%) inadequate due to lack of cellularity. The commonest lesion in the thyroid gland was colloid goiter. Among the malignant neoplasms the commonest was papillary carcinoma. Out of 273 patients, histopathological diagnosis was available in 45 patients. Statistical analysis of our data shows the diagnostic accuracy of fine needle aspiration cytology to be 95.7%. Fine needle aspiration cytology showed a sensitivity of 96.4% and a specificity of 94.4%. Conclusion: Fine needle aspiration cytology is a well established technique for pre operative investigation of thyroid gland swellings with high sensitivity, specificity and accuracy. DOI: http://dx.doi.org/10.3126/jpn.v3i6.8988 Journal of Pathology of Nepal (2013) Vol. 3, 433-436